2003
DOI: 10.1046/j.1365-3040.2003.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses of cotton (Gossypium hirsutum L.) to elevated carbon dioxide and ultraviolet‐B radiation under controlled environmental conditions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 46 publications
12
83
3
1
Order By: Relevance
“…These results are in agreement with previous studies that indicated no UV-B effects on growth under field and growth chamber (HAKADA et al, 2002;ZHAO et al, 2003). In a recent review by KAKANI et al (2003b), shows that in 54% of 40 studies under greenhouse, growth chamber or field conditions reported a redution of biomass by elevated UV-B radiation while 35% of the studies reported no effect.…”
Section: Resultssupporting
confidence: 91%
“…These results are in agreement with previous studies that indicated no UV-B effects on growth under field and growth chamber (HAKADA et al, 2002;ZHAO et al, 2003). In a recent review by KAKANI et al (2003b), shows that in 54% of 40 studies under greenhouse, growth chamber or field conditions reported a redution of biomass by elevated UV-B radiation while 35% of the studies reported no effect.…”
Section: Resultssupporting
confidence: 91%
“…Our results showed that UV-B radiation acts as an important signal allowing P. cathayana seedlings to respond to drought and that the combination of drought and UV-B radiation may cause synergistically detrimental effects on plant growth in both low and high altitude populations. The levels of UV-B radiation used in this study (12.4 kJ m −2 d −1 ) are similar to the amount of radiation experienced in the eastern Himalaya with a 25% stratospheric ozone reduction during a clear day around summer solstice according to a mathematical model by Madronich et al (1995) but lower than the amount expected to occur with a 30% depletion in the stratospheric ozone (15.1 kJ m −2 d −1 ) (Zhao et al, 2003). We conclude that P. cathayana seedlings will show symptoms of an UV-B stress if the intensity of UV-B radiation will increase in the future.…”
Section: The Growth and Physiological Responses As Affected By The Cosupporting
confidence: 65%
“…In such a situation, starch degradation can be the main cause for an increase in WSC. Barsig and Malz (2000) and Zhao et al (2003) observed a decrease in soluble carbohydrates in Zea mays L. (sugar maize) and Gossypium hirsutum L. (cotton), which is contrary to our findings. Additionally, our results show increased WSC, in contrast to some previous studies by Yazawa et al (1992) and Quaggiotti et al (2004).…”
Section: Effect Of Uv-b On the Growth Of V Giganteacontrasting
confidence: 99%